Kembangkan Ekonomi Kreatif Serbuk Jamu UMKM Jamu Mbak Sri Desa Banjaragung, Kabupaten Jombang - Assyifaul Baity Zuraj; Sishadiyati Sishadiyati; Wiwin Priana Primandhana (Cv. Utility Project Solution, 2023)
Jamu is one of the traditional drinks whose existence is still easy to find today. There are various spices whose existence can be used as the main ingredient in making traditioal herbal drinks. Utilizing herbal drink into powder is a solution, so that the storage of herbal medicine is a litte longer and marketing is wider. The innovation of making tamarindand tumeric hers was carried out oer a period of approximately 2 months which was located in Banjaragung. Expanding the reach for consumers is also a consideration for making herbal powder as research conducted by KKN-T 02 UPN “Veteran” Jawa Timur. This study aims to examine further the process of making tamarind turmeric powder.